The linguistic portrayal of the world in English literature: a comparative analysis of Shakespeare’s “Hamlet” and Austen’s “Pride And Prejudice” - Irsalieva , Madinaxon (The Lingua Spectrum, 2025)
This paper conducts an in-depth comparative analysis of the linguistic techniques employed by William Shakespeare in “Hamlet” and Jane Austen in “Pride and Prejudice” to portray the complexities of human experience, societal structures, and philosophical dilemmas. By examining the aesthetic, psychological, and social functions of language in these works, the study highlights how each author uses stylistic devices such as symbolism, irony, soliloquies, and dialogue to construct their fictional worlds. Shakespeare’s Hamlet exemplifies the poetic and philosophical potential of language in tragedy, while Austen’s Pride and Prejudice demonstrates the satirical and social dimensions of prose in the novel form. The paper concludes that both works, despite their differing genres and historical contexts, reveal language as a powerful tool for exploring universal themes of power, morality, identity, and human relationships.